Law Enforcement Against The Criminal Act of Forgery of Documents By a Notary In The Perspective of Law No. 30 of 2004 Concerning The Implementation of Administrative Sanctions or The Notary's Code of Ethics - Sara, Rineke; Trisnaning, Theresia (Jurnal Indonesia Sosial Sains, 2023)
The existence of a notary as a witness or even as a suspect, if it is related to the existence of his position in the legal field which is intended to support the smooth running of a law enforcement process, including the judicial process, would not be a problem, in other words, it is only natural for a notary to act as a witness or even as a suspect in a judicial process. On the other hand, a notary in carrying out his position as a public official, apart from being related to a position regulation, is also related to the oath of office which he takes when appointed as a notary where the notary is obliged to keep the contents of the deed and information he obtains confidential as regulated in Article 4 Paragraph ( 2) Law Number 30 of 2004 concerning the Position of Notary which states that, I will keep confidential the contents of deeds and information obtained in the performance of my office. Further Article 54 Paragraph (1) of Law Number 2 of 2014 concerning Amendments to the Law -Law Number 30 of 2004 concerning the Position of Notary Public explains that a notary can only give, show, or notify the contents of the deed, grosses deed, copy of the deed or excerpt from the deed, to people who have a direct interest in the deed, heirs, or people who have acquired rights, unless otherwise determined by statutory regulations. The exercise of the right to keep secrets related to one's position is also regulated in criminal procedural law, civil law, and the Criminal Code. Article 170 Paragraph (1) of the Criminal Procedure Code states that those who because of their work, dignity, or position are required to keep secrets, can ask to be released from exercising their right to provide information as a witness, namely about matters entrusted to them. This type of research is Normative research. The approaches used are a statutory approach and a conceptual approach. The data source used is secondary data. Data analysis was carried out descriptively and qualitatively. Concluding is carried out using a deductive method from general to specific, especially those related to the research topic, namely law enforcement against the crime of document falsification by notaries in the perspective of Law no. 30 of 2004. This research resulted in the findings of Law Number 30 of 2004 in conjunction with Law Number 2 of 2014 concerning the Position of Notaries which regulates that when a Notary in carrying out his official duties has committed a violation that causes a deviation from the law, the Notary can be subject to sanctions in the form of sanctions. Civil, Administrative, Code of Ethics for Notary Positions. These sanctions have been regulated in such a way both previously and now in the Law on the Position of Notaries regarding the Code of Ethics for the Notary Position profession where there is no description of criminal sanctions but rather the organization of the Notary Supervisory Council which has the authority to impose punishments on notaries. Notaries in carrying out their official duties do not close the possibility of being in contact with legal issues, even though carrying out the duties has been done carefully and by statutory provisions